2020
DOI: 10.1101/2020.09.14.296194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mitochondrial surface receptor Tom70 protects the cytosol against mitoprotein-induced stress

Abstract: SummaryMost mitochondrial proteins are synthesized as precursors in the cytosol and post-translationally transported into mitochondria. The mitochondrial surface protein Tom70 acts at the interface of the cytosol and mitochondria. In vitro import experiments identified Tom70 as targeting receptor, particularly for hydrophobic carriers. Using in vivo methods and high content screens, we revisited the question of Tom70 function and considerably expanded the set of Tom70-dependent mitochondrial proteins. We demon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 120 publications
(137 reference statements)
0
7
0
Order By: Relevance
“…It has recently been shown that the main function of yeast Tom70 is to recruit chaperones to the OM and that import of many soluble matrix proteins also depends on Tom70 ( 41 ). The restored group is significantly enriched for mitoribosomal proteins but depleted for inner membrane proteins and subunits of the oxidative phosphorylation complexes ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that the main function of yeast Tom70 is to recruit chaperones to the OM and that import of many soluble matrix proteins also depends on Tom70 ( 41 ). The restored group is significantly enriched for mitoribosomal proteins but depleted for inner membrane proteins and subunits of the oxidative phosphorylation complexes ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with recent results in yeast, which demonstrated that the most important activity of Tom70 is to recruit cytosolic chaperones to the mitochondrial OM. In fact, tethering of an unrelated chaperone binding domain to the OM complemented most of the defects caused by Tom70 deletion ( 41 ). Whether hydrogenosomes also have two receptors with different substrate specificities, or whether Tom36 and Tom46 are functionally equivalent, is unclear at present.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies reported alternative approaches to follow the import reaction which resulted in surprising observations: (1) Ribosome profiling revealed that cytosolic chaperones and the signal recognition particle play crucial roles in distinguishing mitochondrial and secretory proteins already at very early steps in their synthesis (Schibich et al, 2016;Doring et al, 2017;Costa et al, 2018); (2) proximity labeling suggested that some mitochondrial proteins, in particular hydrophobic inner membrane proteins, explore the mitochondrial surface already during their synthesis (Jan et al, 2014;Williams et al, 2014; Vardi-Oknin and Arava, 2019; Wang et al, 2019) and that, in vivo, many (if not most) mitochondrial surface proteins are in direct proximity to the ER (Hung et al, 2017;Cho et al, 2020); (3) systematic screens of GFP-tagged protein libraries showed that many mitochondrial proteins are prone to accumulate in non-mitochondrial locations under certain growth conditions, in particular on the ER and within the nucleus (Vitali et al, 2018;Backes et al, 2020;Saladi et al, 2020;Shakya et al, 2020;Xiao et al, 2020) and, maybe even more surprising, observed non-mitochondrial residents in mitochondria (Ruan et al, 2017;Bader et al, 2020); and (4) genetic screens reported a very close cooperation of the mitochondrial and ER surface in protein biogenesis (Kornmann et al, 2009;Papic et al, 2013;Okreglak and Walter, 2014;Gamerdinger et al, 2015;Wohlever et al, 2017;Hansen et al, 2018;Vitali et al, 2018;Dederer et al, 2019;Matsumoto et al, 2019). Thus, in vivo, the surfaces of the ER and of mitochondria apparently vividly cooperate to sort proteins to the correct intracellular location.…”
Section: Discussionmentioning
confidence: 99%
“…The following methods were used as described: lipid analysis of yeast cells (Aaltonen et al, 2016;Velazquez et al, 2016); electron microscopy, isolation of mitochondria and import of radiolabeled proteins (Laborenz et al, 2019); mass spectrometry (Backes et al, 2020;Saladi et al, 2020). Fig.…”
Section: Miscellaneousmentioning
confidence: 99%
“…The Tom70 molecules contain two binding sites, one for the precursor and one for the chaperones [ 103 ], and aid in the transfer of the protein to Tom22 for insertion into the Tom40 channel [ 104 , 105 ]. More recently, the biological significance of Tom70 has been challenged, and it is suggested that the receptor acts as a general interface between cytosolic chaperones and the mitochondrial import machinery, and not as a specific receptor for carrier precursors [ 106 ]. In this regard, Tom70 would play a key role in reducing precursor-induced proteostasis stress.…”
Section: Protein Translocationmentioning
confidence: 99%